Marketing in the Green: A Description of Direct Selling and Relationship Marketing in Malaysian Jungles - DR. MOHAMMAD DAUD ALI; DR. SYED IMAD SHAH; MUHAMMAD TARIQ (Journal of Business & Tourism, 2021)
This paper is a description of how marketing occurs in the forests of Malaysia, a focus made on the direct selling and relationship marketing in those jungles where marketers/sales people get access to their customers. These potential customers living in the shelter houses temporarily prepared in the jungles where the customers are employed for various assignments. An observation method for data and information gathering is acquired. Discussion/ unstructured interviews are made with the sales people and customers to understand the essence of direct selling and the relationship that the marketers have developed with the customers who live in the jungles. Also, pictures were drawn with a digital camera to reveal how the customers and the marketers relate while dealing with each other.